2016
DOI: 10.7143/jhep.43.511
|View full text |Cite
|
Sign up to set email alerts
|

Serum ferritin and high sensitivity C-reactive protein are associated with metabolic syndrome in Japanese men and women

Abstract: Objective Ferritin is involved in the occurrence of oxidative stress and regulation of adiponectin, both of which can modulate metabolic syndrome (MetS). To investigate the association of ferritin with MetS in Japanese, a cross-sectional study was conducted involving 324 men and 340 women who underwent anti-aging health checks at Tokai University Tokyo Hospital. Results Ferritin levels were significantly higher in the subjects with hyperglycemia and dyslipidemia in both men and women, and in those with abdomin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Swaminathan et al [27] have reported that iron causes insulin resistance, pancreatic β cell dysfunction, and hepatic dysfunction. Additionally, Yamada et al [28] have reported that serum ferritin level increases as more diagnostic criteria of metabolic syndrome are fulfilled and that ferritin is a potential biomarker in metabolic syndrome. From these findings, the laboratory data related to metabolic syndrome, such as UA, insulin, and ferritin, may also be useful in evaluating the LEL patients and understanding the underlying causes in the idiopathic cases.…”
Section: Discussionmentioning
confidence: 99%
“…Swaminathan et al [27] have reported that iron causes insulin resistance, pancreatic β cell dysfunction, and hepatic dysfunction. Additionally, Yamada et al [28] have reported that serum ferritin level increases as more diagnostic criteria of metabolic syndrome are fulfilled and that ferritin is a potential biomarker in metabolic syndrome. From these findings, the laboratory data related to metabolic syndrome, such as UA, insulin, and ferritin, may also be useful in evaluating the LEL patients and understanding the underlying causes in the idiopathic cases.…”
Section: Discussionmentioning
confidence: 99%
“…In relation to oxidative stress, we reported that ferritin is an important oxidative stress marker. Ferritin is involved in the occurrence of oxidative stress and the regulation of adiponectin, and we demonstrated that ferritin as a potent biomarker for metabolic syndrome 15) . The serum total anti-oxidant status was significantly correlated with uric acid, vitamin A, folate, and valine.…”
Section: Findings From the Anti-aging Health Check-ups At Tokai Unive...mentioning
confidence: 76%
“…In addition, to investigate the relationship of nutrient intake and energy expenditure with obesity, we compared lifestyle habits in obese and non-obese Japanese men by estimating their nutritional intake and energy expenditure values 14) . It was shown that obesity was associated with decreased nonexercise activity thermogenesis (NEAT), and that approaches to enhance NEAT, for example, changes in posture and movement, could have a substantial impact on the prevention and reduction of obesity 15) .…”
Section: Findings From the Anti-aging Health Check-ups At Tokai Unive...mentioning
confidence: 99%